Applications of the Addition of extract and cinnamon leaf flour in the Diet on the Quality of Meat of Catfish - Suardi Laheng; Mia Setiawati; Dedi Jusadi; Muhammad Agus Suprayudi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
This study aimed to evaluate the effect of extract and cinnamon (Cinnamomum burmannii) leaf flourin the diet in increasing quality of meat of catfish (Pangsianodon hypopthalmus). Catfish with a weight of319.64 ± 35.99 g/nets reared in 9 nets with dimension 2x1x1,5 m3 at a density of 15 fish/nets for 60 daysof maintenance. The fish were fed with leaves of cinnamon at a dose that was: 0% cinnamon leaf, 0.1%cinnamon leaf extract, and 1% cinnamon leaf flour. The fish were fed 2 times a day with the feeding rate of3% of the average weight of the body. The results showed the treatment of leaf extract and flour, cinnamoncapable of decreasing levels of body fat, fat meat by 10,31-12,27%, 37,26-50,23%, respectively, compared tocontrols (p<0,05), however, cinnamon leaf extract treatment is more effective in improving the quality ofmeat catfish that looks meat texture compact, white flesh color and a slightly sweet taste.Keywords: cinnamon leaf, meat quality, Pangsianodon hypopthalmus